CONTENTS AND SIGNIFICANCE OF THE CONCEPT OF SOCIAL INFRASTRUCTURE OF SMALL TOWNS (Archive of Conferences, 2020)
This article is devoted to the essence of the social infrastructure of small towns and its theoretical foundations.